1996
DOI: 10.1002/macp.1996.021970417
|View full text |Cite
|
Sign up to set email alerts
|

Cryochemical synthesis and structure of metal‐containing poly(p‐xylylenes): system poly(chloro‐p‐xylylene)‐Ag

Abstract: Polymer films with small Ag-clusters and Ag-nanocrystals were obtained by the cocondensation of Ag and chloro-p-xylylene from the gaseous phase followed by low-temperature solid-state polymerization. UV-Vis spectroscopic data show that the annealing of films at ambient temperature and thereafter at 373 K leads to a sharp rise of the amount of Agnanocrystals by aggregation of small clusters, but the mean size iof the nanocrystals remains practically constant. According to X-ray data, the lattice of Ag-nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
2
19
0
4
Order By: Relevance
“…Cryochemical synthesis is based on low-temperature solid-state polymerization in conditions of frozen molecular mobility in the reacting system. Earlier it was shown that a number of monomers, such as acrylonitrile [18], formaldehyde [19][20][21], or p-xylylene (PX) and its derivatives [22][23][24], polymerize in solid state under g or UV radiation at 77 K and even close to the liquid helium temperature [18,20]. It is suggested that such polymerization is caused by specific supramolecular organization of solid-monomer-containing molecular aggregates, which are precursors of polymer chains [25].…”
Section: Methods Of Solid-phase Cryochemical Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Cryochemical synthesis is based on low-temperature solid-state polymerization in conditions of frozen molecular mobility in the reacting system. Earlier it was shown that a number of monomers, such as acrylonitrile [18], formaldehyde [19][20][21], or p-xylylene (PX) and its derivatives [22][23][24], polymerize in solid state under g or UV radiation at 77 K and even close to the liquid helium temperature [18,20]. It is suggested that such polymerization is caused by specific supramolecular organization of solid-monomer-containing molecular aggregates, which are precursors of polymer chains [25].…”
Section: Methods Of Solid-phase Cryochemical Synthesismentioning
confidence: 99%
“…In UV-Vis spectra of PPX films on a background of the PPX absorption, it is possible to observe only absorption bands of Ag n with n > 15, which, according to reference 9, should be in an "open" range of PPX spectrum at l > 320 nm. Because in this spectral range there are no absorption bands except for the absorption band of Ag nanocrystals, it may be concluded that clusters stabilized in obtained films contain less than 15 atoms [24,44].…”
Section: Polymers Containing Metal Clusters and Nanocrystals Physicalmentioning
confidence: 97%
See 3 more Smart Citations